[AR] Al-Ta’lim al-Mudmaj fi Tarqiyah Maharat al-Lughah al-‘Arabiyyah li Ghayr al-Natiqin biha: Blended Learning to Enhance Arabic Language Skills for Non-Native Speakers (Afaq Lughawiyyah, 2024)
This study aims to explore the role of blended learning in enhancing the Arabic language skills of non-native speakers. The researchers will investigate its different forms, how it works, and its outcomes. The study will use a qualitative approach through desk research using the content analysis technique. The primary data sources will be research studies on blended learning published on Google Scholar between 2011 and 2019. The findings of this study suggest that the different forms of blended learning include the utilization of applications and e-tools. The procedures mostly follow the second design model in Zaitun’s perspective, and the outcomes lead to an enhancement of all Arabic language skills. Additionally, two factors that influence the success of qualification skills will also be identified.